12‐2: High Accuracy In‐Cell Integrated Ambient Light and Color Temperature Sensor LCD. Issue 1 (28th June 2022) - Huang, Can; Bu, Huanhuan; Liu, Shuqi; Song, Jiyue; Niu, Xiaoyan; Tian, Chao; Zhang, Lixin; He, Rui; Zha, Guowei; Liu, Guanghui
Abstract : In this paper, we present a novel integrated light‐dependent sensor which can be used to detect the illuminance and color temperature of the ambient light. Based on the low temperature polysilimn (LTPS) thin film transistor (TFT) process and photosensitivity qf PIN photodiode, the sensor can realize 0–100K lux of the monitor range and an accuracy of 0.5 lux/step. Meanwhile, it can identify the color temperature from 2000 K to 8000 K with an accuracy of ± 250 K. The LCD panel with this optical sensor could adjust brightness and color temperature adaptively according to the ambient light. It saves more space for terminal product which will also facilitates the full screen display.